Effect of sintering temperature and Cu-rich secondary phase on dielectric properties of microwave processed CaCu3Ti4O12 ceramics. (10th September 2017) - Samanta, B.; Kumar, P.; Prakash, C.
ABSTRACT: Effect of sintering at different temperature on dielectric properties of microwave processed CaCu3 Ti4 O12 (CCTO) ceramics have been investigated over the frequency range from 100 Hz to 1 MHz at room temperature. Density (ρ) as well as dielectric constant (ϵr ) increased with the sintering temperature up to 1050°C, beyond that "ρ" and 'ϵr ' both decreased. At 1 KHz, maximum value of dielectric constant (ϵr ) achieved ∼13, 000 with a loss (D) ∼ 0.1. Very weak temperature dependence was found in dielectric constant bellow 150°C. Change in dielectric constant can be explained on the basis of IBLC model in presence of secondary CuO phase.